PENGEMBANGAN TEKS ANEKDOT BERBASIS KEARIFAN LOKAL SEBAGAI ALTERNATIF BAHAN AJAR SMA KELAS X - Danissa Citra Uthami (Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2016)
The curriculum turnover phenomenon, on the one hand is seen as effort to improve the overall quality of education and on the other hand, lead to unpreparedness every aspect of learning, mainly the teaching materials. The presence of new material such as text anecdote in the syllabus, making teachers less prepared for learning. The curriculum 2013 caused problem for teacher in providing text anecdote that actually meet the criteria of teaching materials. Therefore, researcher is trying to help teachers seeking the alternative teaching materials other than those contained in the curriculum 2013 textbook, so teachers do not use the text anecdote carelessly. The local genius values which contained in the text anecdote will be the foundation in effort to build learners who are proud of their nation’s culture. Therefore, researchers use the Research and Development Method to create the pattern of teaching materials development based on local wisdom that can be used in text anecdote learning.Keywords: teaching materials; text anecdote; local wisdom.